1996
DOI: 10.1152/ajpregu.1996.271.5.r1274
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of cytochrome P-450 augment fever induced by interleukin-1 beta

Abstract: Metabolites of cytochrome P-450 are produced in cells when arachidonic acid cascade is activated. Fever genesis depends largely on the cyclooxygenase branch of arachidonic acid cascade, which is caused by many stimuli, such as interleukin (IL)-1, IL-6, and interferon-alpha. To assess the significance of cytochrome P-450 branch in fever, murine recombinant IL-1 beta was bilaterally microinjected (1 ng/microliter) into the medial preoptic area and anterior hypothalamus in conscious rats treated 60 min previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 0 publications
5
16
0
Order By: Relevance
“…4C). Our findings are also consistent with studies in mice showing augmentation of fever by inhibitors of cytochrome P450 epoxygenases (22,23).…”
supporting
confidence: 92%
“…4C). Our findings are also consistent with studies in mice showing augmentation of fever by inhibitors of cytochrome P450 epoxygenases (22,23).…”
supporting
confidence: 92%
“…Studies originally conducted by Nakashima et al in the mid 1990’s suggested a role for EFAs in pyresis and the regulation of body temperature [52]. This led to further work supporting the anti-inflammatory effect of the 11,12-EET regioisomer and demonstration of its ability to inhibit the activation of the NFκB pathway [53].…”
Section: Efas Modulate Pain Signalingmentioning
confidence: 99%
“…Throughout the past few decades the neurobiological effects of EETs have been described albeit sporadically (33, 4849). Here we expand on the novel hypothesis that a major role of EETs and other EFAs is the attenuation of pain.…”
Section: Efas and Seh Inhibitors Block Inflammatory And Neuropathic Painmentioning
confidence: 99%
“…Since PGE 2 causes both pain and inflammation it was logical to try sEH inhibitors as therapeutics for inflammatory pain (2829). The initial indication that EETs and possibly other EFAs are powerful anti-inflammatory molecules came from observations made by Nakashima et al, who described the anti-pyretic properties of endogenous epoxygenase metabolites in the brain (48). This was further supported by Node et al who demonstrated a mechanism of action for EETs in vitro involving the NFkB pathway (50).…”
Section: Efas and Seh Inhibitors Block Inflammatory And Neuropathic Painmentioning
confidence: 99%